Ethics in the public sphere - López de la Vieja, M.ª Teresa (Razón y fe, 2019)
Corruption and fraud concern a significant sector of the population, 23.1%, according to a study conducted by the CIS in 2019. International organizations such as the OECD and the United Nations have warned of the consequences of bad practices. The article focuses on the constructive and formative role of ethics: 1. Seven ethical principles are basic to good public governance and the prevention of practices with a very negative impact on institutional quality; 2.The rules of action, set out in codes and guides to good practice, make it possible to specify and apply the principles. The integrity system is completed with ethics committees; 3. Codes, guides and committees are part of an ethical system or culture for governance in the public sphere and service to citizens.
Keywords: public ethics; principles; codes of ethics; good practices